2021
DOI: 10.3390/ijms22147251
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Potentiates α7 Nicotinic Acetylcholine Receptors and Alleviates Autistic-Like Social Deficits and Brain Oxidative Stress Status in Mice

Abstract: Autistic spectrum disorder (ASD) refers to a group of neurodevelopmental disorders characterized by impaired social interaction and cognitive deficit, restricted repetitive behaviors, altered immune responses, and imbalanced oxidative stress status. In recent years, there has been a growing interest in studying the role of nicotinic acetylcholine receptors (nAChRs), specifically α7-nAChRs, in the CNS. Influence of agonists for α7-nAChRs on the cognitive behavior, learning, and memory formation has been demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…The first one, in which curcumin (20 mg/kg) was administered from PND 6 to 8, reported enhanced neural stem cell proliferation, along with increased sociability and improved short-term memory [ 102 ]. The second study evaluated three different doses of curcumin (25/50/100 mg/kg), showing restoration of different oxidative stress markers in the hippocampus and cerebellum, along with a dose-dependent increase in sociability in curcumin-treated mice [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first one, in which curcumin (20 mg/kg) was administered from PND 6 to 8, reported enhanced neural stem cell proliferation, along with increased sociability and improved short-term memory [ 102 ]. The second study evaluated three different doses of curcumin (25/50/100 mg/kg), showing restoration of different oxidative stress markers in the hippocampus and cerebellum, along with a dose-dependent increase in sociability in curcumin-treated mice [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the theory above, Ma et al [91] prepared Ag44(SR)30 silver nanoclusters with a ligand of 5-mercapto-2-nitrobenzoic acid, and completed the high precision detection of GSH, which enables more accurate and comprehensive diagnosis and assessment of Parkinson's disease. It had been reported that autism spectrum disorders (ASD) were also associated with GSH [92][93][94][95]. The research found that both reduced GSH and total GSH levels were lower in the ASD group than that in the control group [96].…”
Section: Nano-drug Design Based On the Role Of Gsh In Neurological Diseasesmentioning
confidence: 91%
“…Additionally, curcumin at doses of 25, 50, and 100 mg/kg demonstrated improvement in social deficit among BTBR mice without affecting their anxiety‐like behavior and locomotor activity. At doses of 50 and 100 mg/kg, i.p., it also resulted in a marked decrease in oxidative stress by restoring decreased levels of antioxidant enzymes such as catalase and superoxide dismutase in the cerebellum and hippocampus of treated mice (Jayaprakash et al, 2021). Collectively, these findings demonstrate that curcumin potentiates α7‐nAChRs, attenuates oxidative stress, and alleviates ASD‐like characteristics in mice.…”
Section: Autism (Asd)mentioning
confidence: 99%